Sistem Rangkaian Kontrol Bergantian Pada Motor 3 Phasa Menggunakan PLC Siemens S7 1200 - Ade Nurfauziah; Soffan Nurhaji; Jan Manendro Utomo Budiawan (Manutech : Jurnal Teknologi Manufaktur, 2023)
The rapid development of technology has resulted in many real changes in industrial progress, many sophisticated tools and are used in industrial processes with control systems that work automatically without having to be pressured by humans, one of which is a series of alternating controllers, which is a circuit made to carry out control of a circuit. electricity. This research is intended to create a method for circuits in order to make them work sequentially, with existing working principles besides that this control circuit has been automated using a Siemens S7 1200 PLC. Using a research method, namely descriptive experimental research with qualitative methods in its interpretation. Descriptive research because in this study did not use a special method but only the facts that exist and are temporary. The results of this study are Push Button on/start 1 is pressed then the green indicator light (L1/LH) lights up, then Push button on 2 is pressed then the green and yellow indicator lights (L1 GREEN/L2 YELLOW) light up, and Pushbutton Off is pressed then the output is the indicator light will turn off whether it's L1/L2. TOR will be activated immediately and is indicated by a red indicator light flashing, and when the EMG button is pressed, the red indicator light will light up.